The importance of hygiene systems in quality assurance in the meat industry in Gyula - Szalma, István (Animal Welfare, Etológia és Tartástechnológia (AWETH), 2015)
For several years, we selected certain manufacturing sites where we performed hygiene assessments. To determine the hygienic status of a certain site, we collected samples regularly, on a daily basis, from the same places, during working hours. When needed, we proposed ways of improvement and development. We assessed the presence of Salmonella, Listeria monocytogenes, Escherichia coli and Escherichia coli O157. Heat-treated, sliced, vacuum-packed final products and sausages were regularly tested microbiologically, including the detection of Listeria and other food-borne pathogens. The above mentioned studies were conducted between 2004 and 2006, that is, we evaluated the presence of Salmonella, Listeria monocytogenes, Staphylococcus aureus, Escherichia coli and Coliform microbes at the plants and in heat-treated, vacuum-packed final products and sliced, packed dry food. These appraising tests are to define the level of microbiological contamination their results show the base line, meaning the average level of microbiological contamination, for a manufacturing site or an industry. In the selected manufacturing sites (a slaughterhouse and a processing plant) we took samples from pre-determined areas. In the processing plant the samples were taken from different points of the site, from the final product, as well as from the tools and hands of the workers. In the slaughterhouse, the samples were collected from the pork and beef muscle tissues. We selected swab and meat samples to detect Salmonella which proved positive in some cases; at one of the sites Salmonella was detected in the swab sample as well as in the purchased meat. All tissue samples were Salmonella negative. The number of incidence both for Listeria and L. monocytogenes had increased year by year, but sampling was made from the critical points identified during the previous years, which can be an explanation for the increase of incidence in the swab samples. The high number of suppliers is not ideal. The chances of Listeria and Salmonella contamination were higher at the suppliers who were investigated many times. 39,6% of the swab samples and 51,1% of the meat samples were contaminated with S. aureus (2006). These figures are in line with the Staphylococcus contamination level of the halfcarcasses.